(untitled) (Vietnam Journal of Community Medicine, 2020)
Objective: To assess the treament compliance of patients with type 2 diabetes at My Xuyen District’s Medical Center. Subjects and methods: Study of description and analysis on 385 medical records of diabetes at My Xuyen District’s Medical Center, from November 2019 to March 2020. Results: The proportion of patients with type 2 diabetes in women accounted for 64.4%, men accounted for 35.6%, with the average age of 60.0 ± 10.0 years old, the largest age was 92 and the smallest age was 40. Mainly, having 4–7 years of treatment for type 2 diabetes with the rate of 24.9%, patients treated from 1-3 years and >11 years both accounted for 23.6%. Patients treated for 8-11 years was 18.4%. The group of patients with treatment period <1 year and >6 months had the lowest rate, accounting for about 9.4%. There were 71.2% of patients complying well with treatment, the remaining 28.8% of patients surveyed poor compliance. Causes of non-compliance: 67.6% of pateints forgot to take medicine, 43.2% of pateints was too busy with work or family, 25.2% with afraid of side effects of drugs such as abdominal pain and diarrhea. flow, headache, fatigue... Other causes of non-compliance were due to high cost of drugs (17.1%), too many drugs (36.0%), many times to take drugs during days (15.3%). Patients who showed no interest in taking medicines that have been prescribed (22.5%). 22.5% of patients admitted that their poor compliance was due to other reasons. Conclusion: There were 71.2% of patients complying well with treatment, the remaining 28.8% of patients were surveyed poor compliance. The main reasons for non-compliance were due to forgetting to take medicine (67.6%), 43.2% of pateints were too busy with work or family, 25.2% of patients were afraid of the side effects of drugs such as stomachache, diarrhea, headache, fatigue...